(untitled) (Research, Society and Development, 2020)
This article aims to discuss about the curricular political emergence of critical intercultural education in the process of training teachers in Natural Sciences in Brazil aligned with anti-racist education. The perspective of this critical intercultural education proposal is justified by proposing teacher training based on human rights, diversity, religion, gender, respect for differences, sexuality, racial, traditional communities and others The research problem was to investigate the space in the curricular organization of the critical intercultural education in the initial training of teachers in Natural Sciences. The study has a qualitative approach in the objectives of exploratory research and, within the procedures of action research. The results showed the lack of priority in teacher education of curriculum policy from the perspective of critical intercultural education. In the speeches of the researched teachers, there was an emphasis on the monocultural Eurocentric colonial library ensured in the initial training in the area of Natural Sciences. It is concluded that the emergence of curricular policy within the paradigm of intercultural criticism, corroborates for the valorization of the scientific knowledge of indigenous and black africans.